AN EXPERIMENTAL STUDY OF OPSONIC IMMUNITY TO STAPHYLOCOCCUS AUREUS - Meakins, J. C. (The Rockefeller University Press, 1910)
1. The administration of Staphylococcus aureus, killed by heat (vaccine), produces a high degree of opsonic immunity in rabbits. 2. Such increase of opsonin affords protection against living virulent staphylococcus in direct proportion to the amount of opsonins present in the serum and complete recovery may follow subsequent inoculation, if the opsonic power be high. 3. Frequent administration of vaccines may produce a diminution of the opsonic power of the serum. 4. Immune opsonins are most active against the homologous strain of Staphylococcus aureus, but are only slightly less active against heterologous strains. 5. Infections of the human body by Staphylococcus aureus may cause great increase of opsonins. 6. Vaccines prepared from Staphylococcus aureus may produce a high degree of opsonic immunity in man.